LEVELS OF CULTURE SHOCK IN STUDENTS AT UNIVERSITY - Aryani, Neng Desi; Komar, Oong; Abdulhak, Ishak; Hatimah, Ihat; Nuraini, Cut (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2021)
Culture shock is very much related to the situation where someone living in a new environment experiences worries and uncertainties of excessive feelings and thoughts. In the University of Singaperbangsa Karawang (UNSIKA), the presence of culture shock is very apparent among students. This condition is not only motivated by the status of UNSIKA as a State University in Karawang area but also because the position of Karawang City is located on the border of the Capital City, in which it is the center of Metropolitan life. Thus, this situation may affect the social conditions of the community which is later formed a culture shock. There are a big number of students who come to study at UNSIKA from various regions, including outside Java Island. This condition makes culture shock experienced by students at UNSIKA at varying stages.